T-cell exhaustion and stemness in antitumor immunity: Characteristics, mechanisms, and implications - Chi, Xiaoxia; Luo, Shahang; Ye, Peng; Hwang, Wei-Lun; Cha, Jong-Ho; Yan, Xiuwen; Yang, Wen-Hao (Frontiers in Immunology, 2023)
T cells play a crucial role in the regulation of immune response and are integral to the efficacy of cancer immunotherapy. Because immunotherapy has emerged as a promising treatment for cancer, increasing attention has been focused on the differentiation and function of T cells in immune response. In this review, we describe the research progress on T-cell exhaustion and stemness in the field of cancer immunotherapy and summarize advances in potential strategies to intervene and treat chronic infection and cancer by reversing T-cell exhaustion and maintaining and increasing T-cell stemness. Moreover, we discuss therapeutic strategies to overcome T-cell immunodeficiency in the tumor microenvironment and promote continuous breakthroughs in the anticancer activity of T cells.